RESTRUCTURING AS WAY OF ENSURING STABILITY OF DEVELOPMENT OF THE COMPANY - P. V. Aksenov (Стратегические решения и риск-менеджмент)
The urgency of a problem of restructuring of the enterprises is caused by several reasons, main from which are: transition of Russia to market economic system, increase of financial risks of the enterprises in the conditions of market economy, development of competitive fight between the companies and groups of companies in various segments of the market and a number of the deep financial and economic crises which have comprehended the Russian economy for the last fifteen years.The main reason on which enterprise restructuring is carried out, the low overall performance of the company caused by discrepancy of business to changing requirements of the market usually is. Unsatisfactory financial performance, shortage of current assets, high level of receivables and payables become a consequence of a similar situation. So, any updating of scales of business or market conditions demands adequate change of a control system. And far-sighted heads carry out transformations, without waiting decrease in efficiency of business.